2019
DOI: 10.3991/ijoe.v15i15.11688
|View full text |Cite
|
Sign up to set email alerts
|

ECG-based Detection and Prediction Models of Sudden Cardiac Death: Current Performances and New Perspectives on Signal Processing Techniques

Abstract: Heart disease remains the main leading cause of death globally and around 50% of the patients died due to sudden cardiac death (SCD). Early detection and prediction of SCD have become an important topic of research and it is crucial for cardiac patient’s survival. Electrocardiography (ECG) has always been the first screening method for patient with cardiac complaints and it is proven as an important predictor of SCD. ECG parameters such as RR interval, QT duration, QRS complex curve, J-point elevation and T-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Einthoven in 1906 categorized normal and abnormal ECGs that were translated by Cardiologist Henry Blackburn [30]. He discussed the first electrocardiographic tracings of atrial fibrillation 3 , premature ventricular contractions 4 , ventricular bigeminy 5 , atrial flutter 6 . The beginning of ECG related research was also demonstrated in an experimental setup that induced heart block in a dog, as shown in Fig.…”
Section: Ecg Signal (P Wave Qrs Complex T Wave J Point)mentioning
confidence: 99%
See 2 more Smart Citations
“…Einthoven in 1906 categorized normal and abnormal ECGs that were translated by Cardiologist Henry Blackburn [30]. He discussed the first electrocardiographic tracings of atrial fibrillation 3 , premature ventricular contractions 4 , ventricular bigeminy 5 , atrial flutter 6 . The beginning of ECG related research was also demonstrated in an experimental setup that induced heart block in a dog, as shown in Fig.…”
Section: Ecg Signal (P Wave Qrs Complex T Wave J Point)mentioning
confidence: 99%
“…In [5], authors discuss several automatic detection methods for Myocardial Infarctions in their review. Authors in [6] discussed ECG based detection and prediction models leading to sudden death due to cardiac failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It determines the RR-before, RR-after, RR-after-average, RR-before-average, different RR, and the heart rate as six RR-interval features. The RR-interval features are calculated from equations (6)(7)(8)(9)(10)(11), and Figure 2 shows these features.…”
Section: Fig 2 the Between-rr And Rr-interval Featuresmentioning
confidence: 99%
“…Peoples die each year due to cardiovascular disease; arrhythmias are among the primary forms of these diseases [2]. Arrhythmia is a heartbeat abnormality with too fast, too slow, or irregular rhythm [3], [4], and it can be detected and classified by electrocardiograph (ECG) signal [5], [6]. The ECG is the tool for measuring the heart's electrical signal in time sequence.…”
Section: Introductionmentioning
confidence: 99%